Streptococcus pneumoniae Type Determination by Multiplex Polymerase Chain Reaction - Yun, Ki Wook (The Korean Academy of Medical Sciences, 2011)
The purpose of this study was to develop pneumococcal typing by multiplex PCR and compare it with conventional serotyping by quellung reaction. Pneumococcal strains used in this study included 77 isolates from clinical specimens collected from children at Seoul National University Children's Hospital from 2006 to 2010. These strains were selected as they represented 26 different serotypes previously determined by quellung reaction. Molecular type was determined by 8 sequential multiplex PCR assays. Bacterial DNA extracted from cultured colonies was used as a template for PCR, and primers used in this study were based on cps operon sequences. Types 6A, 6B, 6C, and 6D were assigned based on the presence of wciN(β) and/or wciP genes in 2 simplex PCRs and sequencing. All 77 isolates were successfully typed by multiplex PCR assays. Determined types were as follows: 1, 3, 4, 5, 6A, 6B, 6C, 6D, 7C, 7F, 9V, 10A, 11A, 12F, 13, 14, 15A, 15B/15C, 19A, 19F, 20, 22F, 23A, 23F, 34, 35B, and 37. The results according to the PCR assays were in complete concordance with those determined by conventional quellung reaction. The multiplex PCR assay is highly reliable and potentially reduces reliance upon conventional serotyping.